Epigenetic control of sexual phenotype in a dioecious plant, Melandrium album - Janousek, B; Siroký, J; Vyskot, B (Molecular & general genetics, 1996)
Melandrium album (syn. Silene latifolia) is a model dioecious species in which the Y chromosome, present only in heterogametic males, plays both a male-determining and a strict female-suppressing role. We showed that treatment with 5-azacytidine (5-azaC) induces a sex change to androhermaphroditism (an-dromonoecy) in about 21% of male plants, while no apparent phenotypic effect was observed in females. All of these bisexual androhermaphrodites (with the standard male 24, AA + XY karyotype) were mosaics possessing both male and hermaphrodite flowers and, moreover, the hermaphrodite flowers displayed various degrees of gynoecium development and seed setting. Southern hybridization analysis with a repetitive DNA probe showed that the 5-azacytidine-treated plants were significantly hypomethylated in CG doubles, but only to a minor degree in CNG triplets. The bisexual trait was transmitted to two successive generations, but only when androhermaphrodite plants were used as pollen donors. The sex reversal was inherited with incomplete penetrance and varying expressivity. Based on the uniparental inheritance pattern of androhermaphroditism we conclude that it originated either by 5-azaC induced inhibition of Y-linked female-suppressing genes or by a heritable activation of autosomal female-determining/promoting genes which can be reversed, on passage through female meiosis, by a genomic imprinting mechanism. The data presented indicate that female sex suppression in M. album XY males is dependent on methylation of specific DNA sequences and can be heritably modified by hypomethylating drugs.
Keywords: rostliny; Plants; Plant Development; DNA rostlinná; regulace genové exprese u rostlin; azacytidin; rozmnožování; Phenotype; Azacitidine; metylace; DNA, Plant; fenotyp; Methylation; Reproduction; Gene Expression Regulation, Plant; vývoj rostlin